Acceptable Risk in Biomedical Research European Perspectives - Simonsen, Sigmund (International Library of Ethics, Law, and the New Medicine, 2012)
This book is the first major work that addresses a core question in biomedical research: the question of acceptable risk. The acceptable level of risks is regulated by the requirement of proportionality in biomedical research law, which state that the risk and burden to the participant must be in proportion to potential benefits to the participant, society or science. This investigation addresses research on healthy volunteers, children, vulnerable subjects, and includes placebo controlled clinical trials. It represents a major contribution towards clarifying the most central, but also the most controversial and complex issue in biomedical research law and bioethics. The EU Clinical Trial Directive, the Council of Europe's Oviedo Convention (and its Additional Protocol), and national regulation in member states are covered. It is a relevant work for lawyers and ethicists, and the practical approach makes a valuable tool for researchers and members of research ethics committees supervising biomedical research.